Congenital Segmental Intestinal Dilatation: A 25-Year Review with Long-Term Follow-up at the Medical University of Innsbruck, Austria - Sergi, Consolato; Hager, Thomas; Hager, Josef (American Journal of Perinatology Reports, 2019)
Background and Aim Congenital segmental intestinal dilatation (CSID) is a neonatal condition with unclear etiology and pathogenesis. Typically, the newborn with CSID presents with a limited (circumscribed) bowel dilatation, an abrupt transition between normal and dilated segments, neither intrinsic nor extrinsic perilesional obstruction, and no aganglionosis or neuronal intestinal dysplasia. We aimed to review this disease and the long-term follow-up at the Children's Hospital of the Medical University of Innsbruck, Tyrol, Austria.Study Design Retrospective 25-year review of medical charts, electronic files, and histopathology of neonates with CSID.Results We identified four infants (three girls and one boy) with CSID. The affected areas included duodenum, ileum, ascending colon, and sigmoid colon. Noteworthy, all patients presented with a cardiovascular defect, of which two required multiple cardiac surgical interventions. Three out of the four patients recovered completely. To date, the three infants are alive.Conclusion This is the first report of patients with CSID and cardiovascular defects. The clinical and surgical intervention for CSID also requires a thorough cardiologic evaluation in these patients. CSID remains an enigmatic entity pointing to the need for joint forces in identifying common loci for genetic investigations.
Keywords: dilatation; intestine; obstruction; aganglionosis; Hirschsprung's disease; heart defect